Nutrient addition effects on tropical dry forests: a mini-review from microbial to ecosystem scales - Powers, Jennifer S.; Becklund, Kristen K.; Gei, Maria G.; Iyengar, Siddarth B.; Meyer, Rebecca; O' Connell, Christine S.; Schilling, Erik M.; Smith, Christina M.; Waring, Bonnie G.; Werden, Leland K. (Frontiers in Earth Science, 2015)
Humans have more than doubled inputs of reactive nitrogen globally and greatly accelerated the biogeochemical cycles of phosphorus and metals. However, the impacts of increased element mobility on tropical ecosystems remain poorly quantified, particularly for the vast tropical dry forest biome. Tropical dry forests are characterized by marked seasonality, relatively little precipitation, and high heterogeneity in plant functional diversity and soil chemistry. For these reasons, increased nutrient deposition may affect tropical dry forests differently than wet tropical or temperate forests. Here we review studies that investigated how nutrient availability affects ecosystem and community processes from the microsite to ecosystem scales in tropical dry forests. The effects of N and P addition on ecosystem carbon cycling and plant and microbial dynamics depend on forest successional stage, soil parent material and rainfall regime. Responses may depend on whether overall productivity is N- versus P-limited, although data to test this hypothesis are limited. These results highlight the many important gaps in our understanding of tropical dry forest responses to global change. Large-scale experiments are required to resolve these uncertainties.